(untitled) - Bain, Joe Staten (New York, 1968)
This book deals with the organization and working of markets in the United States, and thus with the industrial organization of the most important capitalist or enterprise economy in the world today.
Keywords: Industrial organization (Economic theory),Industries,Industrial policy; United States,United States